Remediation of grassland subsidence and reduction of land occupation with tailings backfill technology: a case study of lead-zinc mine in Inner Mongolia, China - Chen, Xinzheng; Guo, Lijie; Zhou, Yabo; Xu, Wenyuan; Zhao, Yue (Frontiers in Environmental Science, 2023)
The mining industry provides essential mineral resources for human society's development. However, this industry generates a large quantity of waste material while rapidly extracting valuable elements from ore, such as processed tailings. The existence of mined voids will cause surface subsidence, and the surface stockpiling of tailings and waste rocks occupy a large amount of land and the risk of Tailings Storage Facility (TSF) failure. This paper proposes tailings backfill technology to mitigate surface subsidence and provides an alternative disposal method for tailings generated during ore extraction. Tailings backfill technology prepares the slurry by adding a certain amount of cementitious material into the tailings and transporting it to the underground goaf through a pipeline. The backfill slurry could then gradually build up its strength during the hydration of. cementitious material. A case study of a lead-zinc mine in the Inner Mongolia Autonomous Region of China using tailings backfill technology was introduced in detail to solve the problems of grassland collapse caused by mine excavation and environmental damage due to tailings disposal. Spread test and rheological test were carried out to study the flow characteristics of filling slurry and the uniaxial compressive strength (UCS) of backfill was tested as well. The result illustrates that the spread of the filling slurry with a solid content between 72% and 76% and cement-tailings ratio between 1:4 and 1:8 is greater than 14cm, and the UCS of backfill is above 1MPa. The research shows that the tailings backfill technology recycles tailings waste while mitigating surface grassland subsidence and land occupation of waste disposal. Tailings backfill technology can significantly reduce tailings discharge or even achieve no discharge. A leaching test for heavy metal element classification of the backfill sample was carried out. The results show that the heavy metal detection indicators meet the environmental protection standard requirements and will not cause secondary environmental pollution. Therefore, tailings backfill technology can realize green and efficient management of mine waste and has great application and promotion prospects.